Cognitive dysfunction and psychosis: expanding the phenotype of SPG7. Issue 3 (4th May 2021) - Soares, Izadora Fonseca Zaiden; Ciarlariello, Vinicius Boaratti; Feder, David; Carvalho, Alzira Alves De Siqueira
ABSTRACT: Spastic paraplegia type 7 (SPG7) is one of the most common forms of autosomal recessive hereditary spastic paraplegia, which can lead to a hybrid spastic-ataxic phenotype. Recently, novel complicated forms of SPG7, including cognitive and social impairment phenotypes, have been reported. We present a SPG7 case with two pathogenic variants in compound heterozygosity in the SPG7 gene, featuring a cerebellar cognitive affective syndrome with psychosis not yet described in the literature.